2010
DOI: 10.1109/tns.2010.2084103
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Nature of Intermittently Stuck Bits in Dynamic RAM Cells

Abstract: A new method is presented and demonstrated to quantify the leakage currents in Intermittently Stuck Bits (ISB's) in SDRAM's, which have been exposed to neutron or proton irradiation. It is argued that these ISB's are caused by Single Particle Displacement Damage Effects (SPDDE's), in the form of displacement damage complexes comprising one or more damage clusters. The leakage current histories of ISB's are compared with a model of the behavior of the displacement damage complexes believed to cause the ISB's.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…It is worth mentioning that in[13], a few extrapolated DRAM cell leakage current traces exhibiting an RTS behavior are presented.…”
mentioning
confidence: 99%
“…It is worth mentioning that in[13], a few extrapolated DRAM cell leakage current traces exhibiting an RTS behavior are presented.…”
mentioning
confidence: 99%
“…The cross section of samples A1 and D1 was about 2.5 time higher than those of samples A2 and D2. A. M. Chugg et al previously reported that the stuck bits due to displacement damages occurred equally in both the powered and unpowered states [13]; in context, the stuck bits in Fig. 7 are present not exclusively because of the displacement damage effect in the products of manufacturers A and D. Detailed examinations of failing mechanisms with respect to power dependency will be reported further studies.…”
Section: High-temperature Annealing Testmentioning
confidence: 85%
“…However, at a certain annealing temperature, the cross section of the SSBs increased. This increase in stuck bits seemed to be caused by random re-sticking of the displacement damages during annealing [13], [18]. The MSBs increased randomly as well, which could be due to similar reasons as the SSBs, but in the control logic elements.…”
Section: High-temperature Annealing Testmentioning
confidence: 89%
“…Stuck bits in SDRAM have been studied in irradiation experiments using different particle species, such as protons and ions, e.g. in [10]- [13]. There, a common suggested cause for the stuck bits is single particles creating leakage paths from the cell capacitor by displacement damage.…”
mentioning
confidence: 99%
“…There, a common suggested cause for the stuck bits is single particles creating leakage paths from the cell capacitor by displacement damage. In [13], as well as in [14], [15], intermittently stuck bits (ISB) are discussed, which deals with the phenomenon of bits appearing as stuck in some periods of time, when otherwise they can operate normally and return the correct value which was written to the memory cell. Stuck bits are discussed in [16] under the terminology weakened cells, where flight data and ground data are presented.…”
mentioning
confidence: 99%